تأثير مواعيد التقليم الصيفي في نمو وإنتاج أشجار التفاح صنف 'Golden delicious' - ديب, علي; سليمان, سليمان; عبيدو, شوكت (Latakia University Journal -Biological Sciences Series, 2019)
تمّت الدّراسة في عام 2011 م على أشجار تفاح بعمر 15 سنة من صنف 'Golden Delicious'، وشملت أربع معاملات: معاملة حزيران (تقليم شتويّ في شهر شباط + تقليم صيفيّ في أوّل حزيران)، معاملة تمّوز(تقليم شتويّ في شهر شباط + تقليم صيفيّ في أوّل تمّوز)، معاملة آب(تقليم شتويّ في شهر شباط + تقليم صيفيّ في أوّل آب)، والشّاهد (تقليم شتويّ في شهر شباط فقط)، وثلاثة مكرّرات لكلّ معاملةٍ، إذ بلغ عدد الأشجار 24 شجرة. بيّنت النّتائج ما يلي: أثّر التّقليم الصّيفيّ بشكلٍ واضحٍ في زيادة قطر الثّمرة إذ بلغ 6.62 سم في معاملة حزيران الّتي تفوّقت معنويّاً على معاملة الشّاهد (تقليم شتويّ فقط) الّذي بلغ عندها قطر الثّمرة 6.30 سم، وزاد قطر الثّمرة في معاملة حزيران بنسبة (11.25%) مقارنةً مع الشّاهد، وهذا يزيد من حجم الثّمرة وبالتّالي تحسين نوعيّتها التّسويقيّة. لم يؤثّر التّقليم الصّيفيّ في طول الطّرود الخضريّة الحديثة. أدّى التّقليم الصّيفيّ إلى انخفاضٍ معنويٍّ للإنتاج في معاملات التّقليم الصّيفيّ الثّلاث مقارنةً مع الشّاهد، خاصّةً في معاملة حزيران حيث بلغ (21.3 كغ/شجرة) مقارنةً مع الشّاهد (91 كغ/شجرة). أثّر التّقليم الصّيفيّ بشكلٍ واضحٍ في وزن الثّمرة، وتفوّقت معاملة حزيران معنويّاً على بقيّة المعاملات إذ بلغ عندها متوسّط وزن الثّمرة (160.1غ) مقارنةً مع الشّاهد (118.4غ). قلّلت معاملات التّقليم الصّيفيّ الثّلاث معنويّاً من عدد الثّمار، وسجّلت معاملة حزيران أقلّ عددٍ من الثّمار (133 ثمرة/شجرة) مقارنةً مع الشّاهد (768 ثمرة/شجرة)، وبلغت نسبة الانخفاض (38.54-82.68%)، إلّا أنّ معاملتي حزيران وتمّوز زادتا معنويّاً من عدد ثمار الدّرجة الأولى والممتازة على التّوالي. أثّر التّقليم الصّيفيّ إيجاباً في نوعيّة الثّمار إذ تفوّقت معاملة حزيران معنويّاً في محتوى الثّمار من السّكريّات الكّليّة(%) ومن (%T.S.S) على بقيّة المعاملات، كما قلّلت معاملتا حزيران وآب معنويّاً من محتوى الثّمار من الحموضة الكلّيّة (T.A%)، كما ازداد معامل نضج الثّمار في هاتين المعاملتين معنويّاً مقارنةً مع بقيّة المعاملات، كما خفّض التّقليم الصّيفيّ بمعاملاته الثّلاث معنويّاً من محتوى الثّمار من فيتامين C مقارنةً مع الشّاهد، إلّا أنّه لم يكن له تأثيراً معنويّاً في قيم PH للثّمار. This study was carried out at the Center of Kasab Commission for Scientific Agriculture Research in Lattakia during 2011 growing season on fifteen years old apple tree Golden delicious planted in distance of 5x5 meters to study the effect of summer pruning on vegetative growth, yield and fruit quality. The study consists of four treatments: the first: (dormant pruning in February + summer pruning in 1 June, the second: (dormant pruning in February + summer pruning in 1 July, the third: (dormant pruning in February + summer pruning in 1 August, the fourth: (dormant pruning in February as a control with three replicates for each treatment and results showed that Fruit diameter was effected clearly by summer pruning. June treatment was better than the control treatment. It was by (6.62 c.m) compared to (6.30 c.m) for the control treatment. Summer pruning caused increasing of Fruit diameter in June treatment about (11.25%) in the control treatment, which raised fruit size and improved the quality of fruit. Summer pruning had no clear effect on vegetative growth (the length of new shoots). Yield was decreased by summer pruning , especially in 1June treatment (21.3 kg) per a tree compared to (91 kg) per a tree for the control treatment. The weight of fruit was effected clearly by summer pruning. June treatment was better than the control treatment. It was increased (160.1g) compared to (118.4g) for the control treatment. The number of fruit was decreased in summer pruning treatments, June treatment has the lowest by (133 fruit) per a tree compared to (768 fruit) per a tree for the control treatment. Summer pruning caused decreasing of fruits number per a tree about (38.54-82.68%) in the control treatment, but the number of excellent and first degree of fruits was increased in July and June treatments respectively. Summer pruning had positive effects in the quality of fruit. (T.S.S%) and (total sugar%) were increased in June treatment compared to other treatment, but (T.A%) was decreased in June and August treatments, so The coefficient of maturity was increased in June and August treatments compared to other treatment, also (V.C) was decreased in summer pruning treatments which had no clear effect on (PH).